1986
DOI: 10.1007/bf00870978
|View full text |Cite
|
Sign up to set email alerts
|

The acute haemodynamic effects of quinapril, a new non-sulfhydryl angiotensin converting enzyme inhibitor, in patients with severe congestive cardiac failure

Abstract: This study investigates the acute haemodynamic effects of Quinapril (CI-906) a new non-sulphydryl angiotensin converting enzyme inhibitor in 15 patients with refractory congestive cardiac failure. There were 14 males and 1 female mean age 59.5 years. After administration of Quinapril there was a significant reduction in mean arterial pressure (MAP) from 93.1 to 79 mmHg, systemic vascular resistance (SVR) from 1887 to 1349 dyn s cm-5 and PCW from 27.3 to 15.3 mmHg. This was accompanied by an increase in CO from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

1989
1989
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 18 publications
0
6
1
Order By: Relevance
“…Our observations record a significant blood pressure fall up to 10 h post-dose with the maximum fall at 5 h. This contrasts with the earlier times to maximal blood pressure response of 2-2.5 h reported in CHF with 5 mg orally by Holt et al [13] and with 2.5-10 mg orally by Nieminen & Kupari [17]. These uncontrolled studies reported a shorter duration of effect on blood pressure.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…Our observations record a significant blood pressure fall up to 10 h post-dose with the maximum fall at 5 h. This contrasts with the earlier times to maximal blood pressure response of 2-2.5 h reported in CHF with 5 mg orally by Holt et al [13] and with 2.5-10 mg orally by Nieminen & Kupari [17]. These uncontrolled studies reported a shorter duration of effect on blood pressure.…”
Section: Discussioncontrasting
confidence: 96%
“…Previous studies with quinapril in heart failure have shown beneficial haemodynamic changes both acutely [13] and with chronic therapy [14]. While the currently recommended starting dose of quinapril in CCF is 2.5 mg, the timing and extent of the haemodynamic response to this dose are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The haemodynamic effects of quinapril have been assessed in patients with congestive heart failure [15][16][17] and those with hypertension. [18] However, the effects of this drug on cardiac morphology, which are associated with its beneficial haemodynamic effects, require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Three acute and two long-term hemodynamic studies have been completed, [10][11][12] and shown quinapril to demonstrate sustained hemodynamic benefit. A placebo-controlled dose- a, study utilizing 4-wk titration; 0 study utilizing I-wk titration.…”
Section: Quinapril In the Treatment Of Congestive Heart Failurementioning
confidence: 99%